2019
DOI: 10.5530/pj.2019.11.180
|View full text |Cite
|
Sign up to set email alerts
|

Review on Chemical Constituents and Biological Activities of Genus Anthemis

Abstract: Genus Anthemis of Family Asteraceae contains mainly flavonoids, sesquiterpene lactones belonging to germacranolides, eudesmanolides, guaianolides, sterols and essential oils. The Plants of genus Anthemis have been known to have anti-inflammatory, hepatoprotective and antioxidant activities due to their rich contents of important physiological and biological compounds. They are referred to as nature's biological response modifier's and are involved in energy transfer, photosensitization and morphogenesis. Sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
4
1
Order By: Relevance
“…Similarly to the present study, caffeic acid, rutin, naringenin, chlorogenic acid, patuletin, and quercetin have been previously found in A. tinctoria inflorescences. However, apigenin-7-glucoside and rosmarinic acid were not detected in the current study although they were detected by previous authors [ 8 , 9 ].…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…Similarly to the present study, caffeic acid, rutin, naringenin, chlorogenic acid, patuletin, and quercetin have been previously found in A. tinctoria inflorescences. However, apigenin-7-glucoside and rosmarinic acid were not detected in the current study although they were detected by previous authors [ 8 , 9 ].…”
Section: Discussioncontrasting
confidence: 85%
“…The main compounds found in the essential oil are α -eudesmol, γ -cadinol, γ -cadinene, decanoic acid, T-muurolol, 1,8-cineole, and β -pinene [ 6 , 7 ]. Chlorogenic acid, gentisic acid, and rosmarinic acid, as well as the flavonoids apigenin-7-glucoside, patuletin, and quercetin, have been found in the aerial parts of A. tinctoria [ 8 , 9 ]. A new flavonoid, tinctosid, has been identified [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fiber supplementation has shown an effective beneficial effect in the treatment of symptomatic hemorrhoids. In studies with multiple intervals of follow-up, results indicated positive outcomes associated with fiber supplementation concerning issues like prolapse, pain, and itching [8].…”
Section: Fiber Supplementmentioning
confidence: 98%
“…Generally, plants that belong to the genus Anthemis are rich in flavonoids, terpenes, and volatile oils. Thus, these plants usually exhibit anti-inflammatory, hepatoprotective, antioxidant, and anti-cancer properties [5].…”
Section: Introductionmentioning
confidence: 99%